Analysis of the influence of the coronavirus pandemic on elderly people - Chirugu, Gianina (Technium Social Sciences Journal, 2022)
The main aim of the paper is to analyse and present the main effects of the coronavirus pandemic on the elderly. Numerous studies published in the last two years presenting the situation of the elderly during the pandemic have been analysed and compared. The results obtained show that by nature of internal and external factors, the elderly are vulnerable and fragile, which is why this category of population is the most exposed to the psychological, social, medical and economic effects of the pandemic. The loneliness and isolation of the elderly and their limited access to various services have led to real trauma for them. In order to survive the unprecedented conditions, the elderly have developed adaptive coping mechanisms to cope with the crisis situations generated